SAT0228 Study of the disease activity and refractoriness to the treatment in a large spanish multicentric cohort of patients with systemic lupus erythematosus. (23rd January 2014) - Pego-Reigosa, J.; Rúa, I.; Aspe, B.; Galindo, M.; Lόpez-Longo, J.; Calvo, J.; García-Yebenes, M.; Tomero, E.; Uriarte, E.; Fito, C.; Sánchez, A.; Olivé, A.; et al.
Abstract : Background: There is little information about the level of activity and the refractoriness to the treatment of the SLE patients in Spain. Objectives: To study the level of activity and calculate the percentage of SLE patients who are refractory to the therapies. Methods: Patients . SLE patients from the RELESSER Registry with active follow up in a Rheumatology Department. Variables . a) clinical and analytical activity manifestations and b) past and current treatments. Methods . Retrospective study of the data collected at the time of the last evaluation of the patient. a) the SELENA-SLEDAI score is calculated and the SLE activity stratified according to that score, b) the percentage of refractory cases is calculated according to predefined criteria: inefficacyof cyclophosphamide (CYC), use of rituximab, splenectomy or inefficacy of ≥2 immunosupressors (methotrexate, leflunomide, abatacept, anti-TNF, azathioprine, CYC, mycophenolate mofetil and/or mycophenolic acid). Results: 583 patients were included (88.3% females, mean age: 45.5 years, SLE duration: median 111 months). At the time of the study, the most frequent clinical manifestations of activity were mucocutaneous (13.9%) and musculoskeletal (6.3%). The least frequent clinical features were myositis and psychosis (0% both). There was renal or neurological/psychiatric activity in the 7.8% and 2.3% of the patients, respectively. From the analytical perspective, 13.6% of the patients had leukopenia. 27 (4.6%) patients had hypocomplementemia and anti-dsDNA antibodies without any clinical manifestation. The median SLEDAI score was: 2 (range: 0-23). 39.4% of patients had a SLEDAI score =0. SLE disease activity was mild (1-4 points), moderate (5-9) and severe (≥10) in 43.4, 13.2 and 3.9% of patients, respectively. The table shows the treatments for lupus that received the patients in each activity level group. 59 (10.1%) of the patients presented moderate or severe activity in spite of being on corticosteroid and antimalarial treatment. The percentage of refractoriness, according to the definition in the "Methods" section, was 10.3% of the patients. Conclusions: The level of disease activity of the lupus patients followed in Spanish Rheumatology Departments is relatively low. An important percentage of the patients (10.1%) has moderate-severe lupus activity in spite of the use of corticosteroids and antimalarials. The percentage of refractoriness of the SLE might be about the 10% of the patients. Disclosure of Interest: None Declared